Quantum dots in food analysis - Majak, Iwona (Lodz University of Technology Press, 2015)
Several potential, mainly medical applications of quantum dots (QDs), including nanodiagnostics, imaging, targeted drug delivery, and photodynamic therapy have been investigated to date. These fluorescent semiconductor nanocrystals are exceptionally suitable for immunolabeling, cell motility assays, in situ hybridization, as live cell markers due to their high photostability. QDs are adapted to the desired application by conjugation to a recognition moiety, e.g., antibodies, peptides, oligonucleotides or aptamers, or by coating with streptavidin. QDs are applied with other techniques, including polymerase chain reaction (PCR), fluorescence resonance-energy transfer (FRET) analysis, fluorescence in-situ hybridization (FISH) and western blot analysis.